Negara Demokrasi dan Hak Asasi Manusia di Indonesia - Nurhikma Ganti; Emilia Susanti; Ami Nur Dinnia; Amelia Rahmawati; Ananda Tazkia; Dwi Nazwa Adisti (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
Democracy is a civilized and universal manifestation in the world, it is related to human rights and arises from the struggle to defend human dignity. Democracy allows people to have full sovereignty over the government and recognizes human rights. In Indonesia, human rights are the foundation of the country and are upheld because Indonesia is a constitutional state that upholds the dignity of the people. A democratic state is a system of government that allows people to have full sovereignty over the government. The rule of law in Indonesia upholds justice and legal certainty, controls society, ensures that obligations are fulfilled and rights are granted. Human rights are important and significant in Indonesia because the Indonesian legal system values ​​and protects human rights because it is based on the Pancasila Law, which emphasizes the importance of human dignity.